Albany (N.Y.) charter - Albany (N.Y.)
Photograph of the municipal charter (1686 July 22) granted by Thomas Dongan, Earl of Limerick, as colonial governor of New York.
Photograph.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Limerick, Thomas Dongan, -- Earl of, -- 1634-1715.; Albany (N.Y.) -- Charters; New York (State) -- History -- Colonial period, ca. 1600-1775.